Metabolic profiling of antioxidant supplement with phytochemicals using plasma 1H NMR-based metabolomics in humans. (June 2016) - Jang, Hyun-Jun; Kim, Ji Won; Ryu, Sung Ha; Kim, You Jin; Kwon, Oran; Kim, Siwon; Kim, Suhkmann; Kim, Kyu-Bong
Highlights: MP supplementation showed antioxidative effects. Plasma metabolite profiles were changed after MP supplementation. Twenty-seven metabolites were subjected to metabolite profiling. Betaine increased and choline, serine and, threonine decreased by MP supplement. Abstract: Aging and age-related diseases in humans are mainly caused by oxidative stress through over-production of reactive oxygen species (ROS). In our previous study, multi-micronutrient supplement containing antioxidants and phytochemicals (MP) resulted in higher antioxidative activity by increasing plasma folate with resistance to DNA damage and LDL oxidation to subjects. In this study, plasma samples were analysed for metabolomics study using 1 H NMR. The metabolic profiles before MP supplementation and after 8-week MP supplementation were clearly separated based on multivariant analyses of principal component analysis (PCA) and orthogonal partial least square-discriminant analysis (OPLS-DA). Twenty-seven metabolites from variable importance plots were screened before MP supplementation and after 8-week MP supplementation. The 27 metabolites had significantly increased levels of betaine but significantly decreased levels of choline, serine, and threonine after MP supplementation. These results suggested that MP supplementation could activate folate cycle to increase resistance to DNA damages.